(untitled) (Experimental biology, 2016)
The objects of study were: Polygonum aviculare L., Polygonum hydropiper L. and Polygonum amphibium L. The collection, drying, storage of raw materials and sampling for the analysis carried out by the requirements of the State Pharmacopoeia of the Republic of Kazakhstan [1]. Micro- and macroelement composition of plant raw materials were determined by atomic adsorption spectrometer Shimadzu AA-6200 ( «Shimadzu», Japan). The samples for analysis were prepared by the standard technique [2] and the requirements of the Republic of Kazakhstan [1]. Plant raw materials were pulverized and burned in a porcelain crucible at a temperature of 500-600 0C in a muffle kiln to form ash. The ash was dissolved in 1N HNO3 solution and then analyzed by the method. 1 N solution of nitric acid was used as a standard solution. The results are shown in Table 1. Table 1. Macro-and microelement analysis of some plants of the genus Polygonum L. Metal mcg/ml P. amphibium P. aviculare P. hydropiper Na 187.7 14.3 15.5 K 774.6 834.8 828.7 Mg 323.1 160.3 234.5 Cu 0.744 0.094 0.103 Ni 0.101 0.047 0.031 Fe 61.7 6.05 7.71 Mn 15.1 9.41 1.73 Zn 3.93 1.04 0.867 Са 1220.7 268.3 308.2 Cd — 0.037 0.011 Pb — — — The results of the elemental composition of the Polygonum L. in the table indicate content of microelements in the investigated objects does not exceed the maximum allowable standards. [1] However, it is also clear that these species plants of Polygonum L. extracted from the soil the elements that are necessary for life and for the production of the most important groups of biologically active substances (polyphenolic compounds, vitamins, coenzymes). The copper content in the plants is: P. amphibium > P. hydropiper > P. aviculare. Copper demonstrates the phenomenon of bioconcentration, due to the peculiarities of metabolism of P.aviculare . It is known that copper is part of polyphenol composition - activator of biogenesis of phenolic compounds [2,3]. Copper deficiency negatively affects the production of phenolic compounds and pigments, anthocyanins, some vitamins, auxins, proteins. Saponin and alkaloid plants also contain high concentration copper [4]. Copper containing blue squirrel - plastocyanin - takes part in the process of photosynthesis, as natural antioxidants. The zinc content in plants is: P. amphibium > P. aviculare > P. hydropiper. Zinc is actively involved in the physiological processes of plants, as part of the active center of a number of enzymes, including those involved in the biosynthesis of polyphenolic compounds. According to some reports, zinc increases the resistance of plants to drought and hyperthermia [4]. The critical concentration of zinc in plants is 300 mg / kg. Mobility and bioavailability of zinc increase in acidic soils. Nickel (P. amphibium > P. aviculare > P. hydropiper) has a specific effect on a number metalloenzymatic complexes, participating in many biochemical reactions, including the synthesis of biologically active compounds. Nickel activates arginase, oxaloacetatedecarboxylase, is involved in transamination reactions and accelerates oxidation of the sulfhydryl groups to disulfide. Under certain conditions, it inhibits phosphatase. Nickel role was revealed in ribosome structure stabilization [4]. Nickel is a stabilizing factor for the anthocyanin pigments and its significant amounts observed in the flowers flavonoid contained plants [2]. It should be noted that pharmacopoeial plants Polygonum L. also contains lead and cadmium. Concentrations of microelements are quite low in all organs of the plants, which is a measure of the purity of the soil in a place their growing. Potassium, sodium, calcium and magnesium dominate in contained of all plants, but the individual elements in each set is specific and associated with the dominant biologically active substances groups in these species.